A novel tool-input-process-output (TIPO) framework for upgrading to lean 4.0 - C. Koteswarapavan; L. N. Pattanaik (International Journal of Production Management and Engineering)
For more than four decades, Lean Manufacturing (LM) has delivered in terms of waste reduction, productivity and sustainability for the benefit of manufacturers, customers and society at large. In the present era of Industry 4.0 (I4.0), the integration of physical and digital systems is providing huge scope for enhancing the performances of conventional lean tools and practices. Although recent literature has emphasized the integration of lean and Industry 4.0 as Lean 4.0, the mode of integration and basis for selecting technologies need to be explored more. The present paper aims to address this gap and presents a novel Tool-Input-Process-Output (TIPO) approach in which ‘Inputs’ required for the implementation of conventional lean tools are identified and mapped with core characteristics of I4.0 technologies to develop the ‘Process’ for the integration. Exemplified on three prominent lean tools; Just-In-Time (JIT), Jidoka and Heijunka  to illustrate the proposed framework.